PERANAN PANTI ASUHAN DALAM PEMBENTUKAN KARAKTER ISLAMI ANAK PADA PANTI ASUHAN SITTI KHADIJAH KABUPATEN PINRANG - NURHIKMAH, NURHIKMAH; HAMANG, M. NASRI (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2014)
This research is an explanation of islamic religion make attention in the form of outward and inward towards orphans as one of the main indicators for the quality of a personâs religious. Similarly, the act of 1945 by one of the article, which reads: the poor and neglected children maintained by the state, in a brightly lit also showed a high concern for the lives of orphans.As the implementation of the countryâs attention, the government through the ministry of social affairs has provided the institutional and fnancial resources. At the ministry of social affairs, there is one special directorate in charge of fostering orphans, among others, especially by means of the orphanage. One orphanage long-standing and growing signifcant in the management orphanage orphanage is Sitti Khadija Pinrang. Sitti Khadija orphanage Pinrang is the best in Pinrang, even one of the best in South Sulawesi. Orphanage Sitti Khadija Pinrang looks from day to day more and get a good response from the government and the whole society